High Concentrations of Serum Soluble E-Cadherin in Patients With Q Fever - Mezouar, Soraya; Omar Osman, Ikram; Melenotte, Cléa; Slimani, Camélia; Chartier, Céline; Raoult, Didier; Mege, Jean-Louis; Devaux, Christian A. (Frontiers in Cellular and Infection Microbiology, 2019)
Cadherins switching is a hallmark of neoplasic processes. The E-cadherin (E-cad) subtype is one of the surface molecules regulating cell-to-cell adhesion. After its cleavage by sheddases, a soluble fragment (sE-cad) is released that has been identified as a pro-carcinogenic inflammatory signal in several bacteria-induced cancers. Recently we reported that Q fever, a disease due to Coxiella burnetii infection, can be complicated by occurrence of non-Hodgkin lymphoma (NHL). Therefore, we studied E-cad switching in Q fever. The sE-cad levels were found increased in the sera of acute and persistent Q fever patients, whereas they remained at the baseline in controls groups of healthy donors, people cured of Q fever, patients suffering from unrelated inflammatory diseases, and past Q fever patients who developed NHL. These results indicate that sE-cad can be considered as a new biomarker of C. burnetii infection rather than a marker of NHL-associated to Q fever. We wondered if changes in sE-cad reflected variations in the CDH1 gene transcription. The expression of E-cad mRNA and its intracellular ligand -catenin was down-regulated in peripheral blood mononuclear cells (PBMCs) of patients with either acute or persistent forms of Q fever. Indeed, a lower cell-surface expression of E-cad was measured in a minority (less than 5%) subpopulation of HLADR+/CD16+ monocytes from patients with acute Q fever. However, a very strong increase in E-cad expression was observed on more than 30% of the HLADR+/CD16+ monocytes of persistent Q fever patients, a cell subpopulation known to be a target for C. burnetii in humans. An experimental in vitro infection of healthy donors' PBMCs with C. burnetii, was performed to directly evaluate the link between C. burnetii interaction with PBMCs and their E-cad expression. A significant increase in the percentage of HLADR+/CD16+ monocytes expressing E-cad was measured after PBMCs had been incubated for 8h with C. burnetii Nine Mile strain. Altogether, these data demonstrate that C. burnetii severely impairs the E-cad expression in circulating cells of Q fever patients.